Identification of Domains and Factors Involved in MINIYO Nuclear Import - Contreras, Ramon; Kallemi, Paraskevi; González-García, Mary Paz; Lazarova, Aleksandra; Sánchez-Serrano, José Juan; Sanmartín, Maite; Rojo, Enrique (Frontiers in Plant Science, 2019)
The transition of stem cells from self-renewal into differentiation is tightly regulated to assure proper development of the organism. Arabidopsis MINIYO (IYO) and its mammalian orthologue RNA Polymerase II Associated Protein 1 (RPAP1) are essential factors for initiating stem cell differentiation in plants and animals. Moreover, there is evidence suggesting that the translocation of IYO and RPAP1 from the cytosol into the nucleus functions as a molecular switch to initiate this cell fate transition. Identifying the determinants of IYO subcellular localization would allow testing if, indeed, nuclear IYO migration triggers cell differentiation and could provide tools to control this crucial developmental transition. Through transient and stable expression assays in Nicotiana benthamiana and Arabidopsis thaliana we demonstrate that IYO contains two nuclear localization signals (NLSs), located at the N- and C-terminus of the protein, which mediate the interaction with the NLS-receptor IMPA4 and the import of the protein into the nucleus. Interestingly, IYO also interacts with GPN GTPases, which are involved in selective nuclear import of RNA polymerase II. This interaction is prevented when the G1 motif in GPN1 is mutated, suggesting that IYO binds specifically to the nucleotide-bound form of GPN1. In contrast, deleting the NLSs in IYO does not prevent the interaction with GPN1, but it interferes with import of GPN1 into the nucleus, indicating that IYO and GPN1 are co-transported as a complex that requires the IYO NLSs for import. This work unveils key domains and factors involved in IYO nuclear import, which may prove instrumental to determine how IYO and RPAP1 control stem cell differentiation.